Journal of Emergency Nursing November 2016, Volume 42, Number 6 - Emergency Nurses Association (Elsevier, 2016)
- Implementing an ED Critical Incident Stress Management Team - Toxic Megacolon: A Review for Emergency Departement Clinicians -...